How perceived organizational support, identification with organization and work engagement influence job satisfaction: A gender-based perspective - Carla Mascarenhas; Anderson Rei Galv\~ao; Carla Susana Marques (Administrative Sciences, 2022)
The main objective of this study is to analyze the effects of work engagement, identification with an organization and perceived organizational support on job satisfaction and how these issues vary with gender. Data were collected in a public higher education institution with a questionnaire applied to professors and support staff. The data collected from the 171 employees allowed the development of a structural equation model. The results suggest that work engagement constructs have a greater effect on job satisfaction for female employees, whereas the impact of perceived organizational support on job satisfaction is stronger for male workers. The analysis also revealed that identification with the organization does not influence job satisfaction differently in terms of gender. The findings of this study contribute to the body of empirical knowledge on how the influence of factors on job satisfaction, such as engagement at work, perceived organizational support and identification with the organization, varies by gender.
Keywords: 350; gender; job satisfaction; organizational identification; perceived organizational support; work engagement